Health Care Expenditure of Patients With Type 2 Diabetes Mellitus in Bangladesh: A Review - Zaman, Md Saif; Hassan, Parvez; Islam, S M Shahinul; Ullah, Md Anayet; Rabbani, Md Golam (Journal of Bio-Science, 2024)
The main objectives of this review are to offer an in-depth examination of the analysis of health care expenditure of patients with type 2 diabetes mellitus in covering its epidemiology, causes, clinical manifestations, diagnostic techniques, treatment approaches, and prognosis in Bangladesh. Most of the information and data are mainly involved in a critical review of various studies from sample groups of different ethnicities, age groups and genders. This study employs a systematic review and meta-analysis approach to compile and analyze existing research on health care expenditure of patients with type 2 diabetes mellitus. The study follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to ensure comprehensive and transparent reporting of the review process. Results on the basis of various reports showed that the length of diabetes and the number of co-morbidities and complications raise the cost of healthcare. The data confirms the previously reported conclusion that patients treated with insulin monotherapy or an insulin and oral hypoglycemic agents (OHAs) combination had higher direct costs and overall costs than patients treated with OHAs alone. Overall, it was discovered that the main contributing factors to the cost of therapy were the length of diabetes, the quantity of co-morbidities and complications, and the type of treatment. The prevalence of type 2 diabetes is increasing in Bangladesh, where out-of-pocket medical expenses are higher and universal health insurance is not available to the general public. Planning cost-effective diabetes management and prevention measures is necessary. A suitable insurance plan should be created with special services for diabetic patients. To reduce the negative effects of the condition, early detection of diabetes is essential as reported by several studies compiled herein. This can be accomplished through raising awareness and eradicating the social stigma, especially for women in Bangladesh. J. Bio-Sci. 32(2): 93-106, 2024